(1070) Regionalization as a Tool of Economic Policy. Part I,II الهيكلة الإقليمية كأداة للسياسة الاقتصادية. (جزءين) - Siegfried Voigtsberger. (INP., 2020)
The topic of the study permits various approaches. The one, actuality chosen in this paper, is to analyze the social and economic factors and forces, which influence the spatial organization of the society and its economy and which therefore have to be taken into account in economic regionalization.That is the reason why so much emphasis put on the theoretical – economic structure and its development tendencies. In part one of the study in mainly concerned with this problem. Part two, is founded on this bases and deals with problems, raised in the process of planning and management, in particular with the relationship between the time orison of planning and regionalization with independency between the administrative territorial structure and regionalization